Utilization Of Composted Organic Waste As Growing Media For Pakcoy (Brassica Rapa Var. Chinensis) Efforts To Reduce Agricultural Environmental Impact - Anisya, Shinta; Winandari, Ovi Prasetya; Khusniyah, Lailatul; Pradana, Satria Adi (WISE Pendidikan Indonesia, 2025)
This study aims to analyse organic waste compost as an effective growing medium and evaluate its effect on the growth of pakcoy (Brassica rapa var. Chinensis) plants. In this study, we focused on analysing the content of macro and micro nutrients required by pakcoy plants, such as C, N, P, K, and Ca. We used a Randomised Group Design (RAK) with two factors: growing media (sawdust, cocopeat, husk charcoal) and organic waste compost concentration. The observation parameters include the development of pakcoy plants, namely plant height, number of leaves, and stalks of pakcoy that have been planted in organic waste compost media.The results showed that organic waste compost with a mixture of sawdust and the addition of EM4 has a nutrient content that is in accordance with the Indonesian National Standard (SNI). In addition, the organic waste compost had a more significant effect on pakcoy growth. Thus, this study shows the potential of using organic waste compost as an alternative to chemical fertilisers in vegetable cultivation. These results can help improve soil fertility and yield of vegetable crops, as well as contribute to the development of sustainable agriculture that is more environmentally friendly.